Performance of Compressed Natural Gas (CNG) Engine with Pre Chamber - M. S., Ali; M. T., Musthafah; A. M., Mohd Shafei; A. M. T., Khairil; N. F. M., Noordin; R. A., Bakar (Centre for Advanced Research on Energy, UTEM, 2016)
Pre chamber is use to extend lean limit of mixture and improve combustion efficiency. Pre chamber used in this study was pre chamber without auxiliary fuel. Then, this pre chamber was applied to single cylinder compressed natural gas engine. The effects of pre chamber on CNG performance are increase in power and torque starting at engine speed 3000 rpm. However, disadvantage by the pre chamber had been discovered on the brake specific fuel consumption (BSFC). It caused the BSFC by CNG was higher than a CNG without pre chamber.